The Status of a Guardian for Children Born Out of Wedlock from the Perspective of the Four Sunni Schools of Law: An Analysis of Hadiths on Guardianship - Ahmad Muhajir Al Musafir (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the position of guardians of marriage for children born out of wedlock from the perspective of the four schools of fiqh (Hanafi, Maliki, Shafi'i, and Hanbali) through the analysis of guardianship hadiths. The background of this research departs from the increasing cases of out-of-wedlock pregnancies that cause legal problems, especially in the determination of marriage guardians, both in social practices of the community and in the implementation of state administration. Differences in views in the community regarding the use of guardians or guardians of judges have the potential to cause legal ambiguity and deviations from the principles of Islamic law. This research is a library research with a qualitative approach. Data was obtained from primary sources in the form of the Qur'an and hadiths of the Prophet Muhammad (saw) related to marriage guardianship, as well as secondary sources in the form of madhhab jurisprudence, books, and scientific journals. Data analysis was carried out in a descriptive-analytical manner by comparing the views of the four schools of fiqh and reviewing them through the approach of maq??id al-syar?'ah, especially in maintaining nasab (?if? al-nasl), honor (?if? al-'ird), and the welfare of children. The results of the study show that the majority of scholars from the Maliki, Shafi'i, and Hanbali schools, as well as strong opinions within the Hanafi schools, agree that children born out of wedlock do not have a guardian of the nasab because there is no legal relationship with the biological father.